(3eTcGI GdeUHGM GdeZfj Yf GdVhA hGdEaJJGMs
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ bdhHfG HeUGHjM GdYde hGdMceI hHYO agPg ChQGb cJHJgG dTQM GdeUHGM eSJYjfkG HNGdb GdEUHGM hSejJgG HeTcGI GdeUHGM s
(3BNQgG (B:s
(3Ci ai GdbSe GdChd GdOGd Ydi GdeVeQ hgh bhdg JYGdi (B( (3bd Hd edI EHQGgje MfjakG (B) (3eG SHb ef GdcdGe hgh ebOe Ydi GdeVeQ gPG BNQ eG cJHJg ef GdChQGb ai TQM GdeUHGM JeJ GdcJGH HYhf Gddg Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B488 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1709s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs